Longitudinal Associations of Leptin and Adiponectin with Heart Rate Variability in Children - Van De Wielle, Roos; Michels, Nathalie (Frontiers in Physiology, 2017)
For early prevention of cardiovascular disease, early detection and risk factor insights are necessary. The autonomic balance reflects cardiovascular risk and can be measured by heart rate variability (HRV). Therefore, our purpose is to examine associations between HRV and the energy-related biomarkers leptin and adiponectin in children. Participants of this study were Belgian children recruited for the longitudinal ChiBS study (year 2010-2012). HRV was measured and fasting blood samples were taken in 249 children at baseline (4.4-11.0y ) and 223 children at follow-up (6.7-12.2y). Cross-sectional and longitudinal linear regression analyses were separated by sex and adjusted for age, socio-economic status, body fat%, negative emotions, puberty and mean heart rate. Leptin was a negative cross-sectional and longitudinal predictor of parasympathetic activity in boys; while leptin in girls was cross-sectionally associated with higher LF and LF/HF suggesting sympathetic predominance. Adiponectin was a negative cross-sectional and longitudinal predictor of parasympathetic activity in boys; but when adjusting for mean heart rate, this effect disappeared and adiponectin was a positive cross-sectional and longitudinal predictor of parasympathetic activity in girls. These results stress the importance of considering sex differences and adjustment for heart rate in testing HRV predictors. Leptin seemed disadvantageous for the autonomic balance, while adiponectin seemed advantageous for the autonomic balance in girls only. More research is needed to see whether leptin and adiponectin are interesting in cardiovascular screening/prevention or in determining the cardiovascular gain during weight loss follow-up.